Ophthalmic viscosurgical device interaction with two hydrophobic acrylic intraocular lenses of different equilibrium water content - Auffarth, Gerd U.; Schickhardt, Sonja; Fang, Hui; Wang, Qiang; Khoramnia, Ramin; Yildirim, Timur Mert (Scientific reports, 2022)
Ophthalmic viscosurgical device (OVD) is used during intraocular surgery to protect ocular tissue. It requires complete removal from the eye by the end of surgery to avoid postoperative complications. This study compares the interaction of a cohesive OVD with two different intraocular lenses (IOLs) of different equilibrium water content. In this laboratory study on porcine cadaver eyes, the capsular bags and anterior chambers of each eye were filled with fluorescein-stained OVD. Following implantation of 10 IOLs each of Clareon CNA0T0 and AcrySof SN60WF (Alcon Laboratory, Fort Worth, USA) IOLs, the OVD was removed using the irrigation/aspiration mode. The OVD removal was timed and differences between the both IOL groups were compared. OVD removal time ranged from 18 to 40 s (mean ± SD, 26.4 ± 6.8 s) and from 16 to 39 s (mean ± SD, 23.6 ± 6.6 s) for eyes implanted with a CNA0T0 and a SN60WF IOL, respectively, without a statistically significant difference between the groups, P > 0.05. Cohesive OVD removal times were similar between the CNA0T0 and SN60WF groups. Surgeons should experience no differences regarding the interaction between cohesive OVDs and IOLs made from the new Clareon material compared to the established AcrySof material.